Detection of low energy antiproton annihilations in a segmented silicon detector - Aghion, Stefano; Bräunig, Philippe; Cerchiari, Giovanni; Kellerbauer, Alban (Journal of Instrumentation, 2014)
The goal of the AEḡIS experiment at the Antiproton Decelerator (AD) at CERN, is to measure directly the Earth's gravitational acceleration on antimatter by measuring the free fall of a pulsed, cold antihydrogen beam. The final position of the falling antihydrogen will be detected by a position sensitive detector. This detector will consist of an active silicon part, where the annihilations take place, followed by an emulsion part. Together, they allow to achieve 1% precision on the measurement of ḡ with about 600 reconstructed and time tagged annihilations. We present here the prospects for the development of the AEḡIS silicon position sentive detector and the results from the first beam tests on a monolithic silicon pixel sensor, along with a comparison to Monte Carlo simulations.